Photophysical characterization of chosen Ln(III) macromolecular complexes - Krzysztof Staninski; Stefan Lis (International Journal of Photoenergy)
Spectral characterization of N,N′-Bis(2,4-dihydroxobenzylidene)1,2-diaminobenzene (DHDA) complexes with chosen f- and d-metal ions are described. Physico-chemical properties of a series of complexes were studied in methanol solution using UV-VIS, IR and fluorescence spectroscopy. It was found that the excitation and fluorescence spectra of DHDA in water and methanol after being exposed to ultraviolet radiation, show very obvious photochromism. The formation of 1 : 1 complexes between 4,4′,4″,4‴-(porphine-5,10,15,20-tetrayl)-tetrakis benzoic acid, (TCPPH2) and La(III), Eu(III) and Yb(III) in methanolic solution, with the use of the spectrophotometric and spectrofluorimetric methods. The conditional stability constants of the complexes were studied by monitoring the spectral changes of energy and intensity of Q bands of the porphyrin.